Hubungan believing dan belonging sebagai dimensi religiusitas dengan lima dimensi well-being pada mahasiswa di Tangerang - Saputra, Andy; Goei, Yonathan Aditya; Lanawati, Sri (Konsorsium Psikologi Ilmiah Nusantara, 2016)
Recent studies showed that well-being has been decreasing in both Asia and the United States of America. Another study found that college students’ well-being was also declining. These findings suggest that ways to increase well-being become very crucial to be explored, such as exploring what variables that correlates or affect it. Previous findings found that religiosity, specifically believing and belonging dimension, affects well-being. This study explore how believing and belonging correlates with well- being and its five dimensions, positive emotions, engagement, positive relationships, meaning, and accomplishment among 181 college students. The result shows that both believing and belonging correlates with the five dimensions of well-being significantly,meaning that the belief in God and belonging into religious groups helps individual’swell-being to flourish.